Estimating Bedrock Depth Based on Total Magnetic Field Anomaly Data in Medan City Area in the Northern Sumatra Basin Using the Peter Half Slope Method - Rasimeng, Syamsurijal; Sianturi, Rizky J.; Surbakti, Lucky Dolinta; Kurniawan, Yoga; Dani, Ilham; Rustadi, Rustadi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
The Peter Half Slope method is valuable for estimating rock depths using total magnetic field anomaly data. It relies on graphical analysis and practical rules to gauge the depths of magnetic sources. This method finds significant utility in magnetic interpretation, measuring half the maximum slope distance on magnetic anomaly curves. The primary objective of this research is to determine anomaly depths within Medan City by applying the Peter Half Slope method. The study employs total magnetic field anomaly data from the Medan city area, a part of the Northern Sumatra Basin. The research methodology includes data preparation, reduction to the pole transformation, profile creation, maximum slope computation, half-slope determination, and identifying tangent points on both minimum and maximum curves. The difference between these tangent points is then calculated to derive the depth of the bedrock. Based on the depth calculations using criteria for very thin, intermediate thickness, and very thick bodies, depths of 401, 301, and 240 meters were obtained, resulting in an average depth of 314 meters. This method plays a pivotal role in characterizing subsurface rock structures and is essential for geophysical analysis and magnetic data interpretation.